Wali Mafqud bagi Perempuan dalam Kajian Hukum Perkawinan dan Keluarga Islam di Indonesia - ulfa safira soliha (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The issue of wali mafqud constitutes an important concern in Islamic family law when a lineage guardian, particularly the biological father, cannot be located and is therefore unable to exercise guardianship in marriage. This situation frequently occurs in Indonesia due to population mobility, divorce, and the breakdown of family communication. This study analyzes the mechanism for replacing a wali mafqud from the perspectives of Islamic law and Indonesian positive law, as well as its relevance in marriage practices. The research employs a qualitative method with a normative-juridical approach through the analysis of fiqh literature, hadith and the Compilation of Islamic Law (KHI). The findings indicate that guardianship authority is transferred to the wali hakim based on the principle of public interest (maslahah), in accordance with the Shafi‘i school and Articles 22–23 of the KHI, to ensure the validity of the marriage contract and the protection of women’s rights.